The current state of left ventricular assist devices: challenges facing further development. (2nd November 2015) - Schumer, Erin M; Ising, Mickey S; Slaughter, Mark S
Abstract : Heart failure is a clinical syndrome with significant morbidity and mortality. The use of left ventricular assist devices has improved outcomes for patients with advanced heart failure in the face of limited donor organs available for heart transplantation. This article describes current issues and limitations facing the left ventricular assist device field and explores how the field can be expanded in this setting.